Development and evaluation of an inhalable nanoemulsion system for enhancing NK cell function against osteosarcoma pulmonary metastases - Hwang, Sookyung; Bates, Paul D.; Valkanioti, Vasiliki; Chang, Chih-Chun; Mecozzi, Sandro; Capitini, Christian M. (Frontiers in Immunology, 2026)
IntroductionOsteosarcoma frequently metastasizes to the lungs, significantly reducing survival in pediatric and young adult patients, with current therapies having limited efficacy. This study aimed to develop an inhalable nanoemulsion formulation to enhance targeted pulmonary drug delivery and restore natural killer (NK) cell-mediated immunity against metastatic osteosarcoma.MethodsA nanoemulsion composed of medium-chain triglyceride (MCT) oil and Distearoyl-rac-glycerol-PEG2000 (DSG-PEG2000), yielding droplets consistently smaller than 200 nm, was designed with demonstrated stability (>550 days), biocompatibility, mucus penetration ability, minimal toxicity on respiratory epithelium, and efficient cellular uptake. To enhance NK cell function in the osteosarcoma tumor microenvironment, the nanoemulsion was loaded with SIS3, a SMAD3 inhibitor targeting immunosuppressive TGF-β signaling, and conjugated with a cysteine-modified form of the NK-cell killer immunoglobulin-like receptor (KIR) antagonist nonamer peptide VAPWNSDAL (VAP–DAC) to block inhibitory LILRB1/ILT-2 on NK-92 cells.ResultsThe resulting SIS3-VAP–DAC nanoemulsion maintained particle sizes below 162 nm, stability over one month, enhanced cytotoxicity of human NK-92 cells, and restoration of granzyme B secretion despite TGF-β suppression, as well as induced NKG2D ligand expression on murine osteosarcoma cells. Intranasal administration of the SIS3-VAP–DAC nanoemulsion effectively reduced pulmonary tumor burden in human osteosarcoma xenograft mouse models with no observable clinical toxicity.DiscussionThis study establishes a novel inhalable nanoemulsion platform that significantly restores NK-cell functionality against pulmonary metastatic osteosarcoma.